F Formulasi Sediaan Lip Serum Minyak Argan (Argania spinosa L.) Dan Uji Efektivitas Sebagai Moisturizing Agent Secara In Vitro - Yandriyani, Devilke (LPPM Universitas Sari Mulia, 2024)
Background: The problem of dry and chapped lips is often experienced by women. This is due to a lack of nutrition and care for the lips, so there is a need for cosmetic products that can be used to moisturize and nourish the lips from the outside and inside. Argan oil is a natural ingredient that has the potential as a moisturizing agent which can be formulated into a lip serum preparation that can moisturize and nourish the lips. This research aims to determine the most optimal formula and concentration of argan oil and its effectiveness as a moisturizing agent.Objective: To determine the effectiveness of argan oil lip serum preparations as a moisturizing agent in vitro.Method: The method used was a true experiment using the Sorption Desorption Test (SDT) and analyzed using a one-way Anova test with p-value <0.05. The lip serum preparation formula is designed using 5 formulas with different concentrations of argan oil, namely 0%, 15%, 20%, 25% and 30%.Results: The effectiveness value was calculated by the total [AUC] value determined by the amount of weight lost during storage. The smaller the weight lost, the greater the effectiveness of the moisture, and vice versa. The results of observations of effectiveness tests on lip serum preparations of argan oil with a concentration of 30% had the smallest weight loss and the highest total [AUC] value. Based on the results of statistical tests, it shows that there is a significant difference with a p-value of 1.5938E-08 (p-value < 0.05).Conclusion: In this study there were significant differences in the effectiveness of the moisture of 5 (five) formulas. Argan oil lip serum preparations with a concentration of 30% have the best moisturizing ability.